The witch [videorecording (DVD)] - Eggers, Robert, 1983-; Taylor-Joy, Anya, 1996-; Ineson, Ralph, 1969-; Dickie, Kate (Lionsgate, 2016)
A family in 1630s New England faces destruction by the forces of witchcraft, black magic, and possession. When one of their five children goes missing and their life-sustaining crops fail, they fall victim to paranoia and fear as they begin to turn on one another.